Pendekatan REBT (Rasional Emotive Behavior Theraphy) untuk Meningkatkan Motivasi Belajar Siswa - Habsy, Bakhrudin All; Cahyo, Ach. Tegas Tri; Jelita, Rania Surya; Fadhilla, Intan Nur (TSAQOFAH, 2024)
The Rational Emotive Behavioral Therapy (REBT) approach is the view that all people have a tendency to think irrationally and this can be achieved through social learning. Rational Emotive Behavioral Therapy (REBT) aims to eliminate emotional disorders that have a negative impact on a person, because they can cause emotions such as anxiety, hatred, fear, and anger, etc. Motivation is one of the factors that influences student performance. The motivation that students get encourages them to study harder, be persistent and have full concentration in the learning process. The type of research used in this research is library research. The aim of this research is to determine the REBT (rational emotive behavior therapy) approach to increasing student learning motivation. The data collection technique used in this literature study is documentation technique, namely searching for data about a thing or variable in the form of notes, books, essays, or articles. The data analysis technique used is content analysis technique. Content analysis research involves the process of selecting, comparing, combining, and rearranging different meanings until relevant meanings are found. From the research results it can be concluded that the "REBT (rational emotional behavior therapy) approach can be used to increase student learning motivation, thereby increasing learning motivation in students with low learning motivation".